Tsp66E, the Drosophila KAI1 homologue, and Tsp74F function to regulate ovarian follicle cell and wing development by stabilizing integrin localization. - Han, S.Y.; Lee, M.; Hong, Y.K.; Hwang, S.; Choi, G.; Suh, Y.S.; Park, S.H.; Lee, S.; Lee, S.H.; Chung, J.; Baek, S.H.; Cho, K.S. (FEBS Letters, 2012)
The metastasis suppressor KAI1/CD82 has been implicated in various cellular processes; however, its function in development is not fully understood. Here, we generated and characterized mutants of Tsp66E and Tsp74F, which are Drosophila homologues of KAI1/CD82 and Tspan11, respectively. These mutants exhibited egg elongation defects along with disturbed integrin localization and actin polarity. Moreover, the defects were enhanced by mutation of inflated, an ?PS2 integrin gene. Mutant ovaries had elevated ?PS2 integrin levels and reduced endocytic trafficking. These results suggest that Drosophila KAI1/CD82 affects the polarized localization and the level of integrin, which may contribute to epithelial cell polarity.